The Effectiveness of the Post-Disaster Population Relocation Policy Following the Galodo Disaster in Nagari Bukik Batabuah, Agam Regency - Siti Nurhaliza; Rahmadhona Fitri Helmi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the effectiveness of post-disaster relocation policy following the Galodo disaster in Nagari Bukik Batabuah, Canduang District, Agam Regency. The issue arises from the gap between the government’s objective to protect affected residents by relocating them to safer areas and the reality that many residents still choose to remain in disaster-prone zones. This study aims to analyze the implementation effectiveness of the relocation policy and identify the factors influencing its effectiveness. The research used a descriptive qualitative method, with data collected through interviews, observation, and documentation. The analysis was based on the organizational effectiveness theory of Richard M. Steers, which includes goal achievement, integration, and adaptation. The results show that the relocation policy has not been fully effective. In terms of goal achievement, the government has provided permanent housing and relocated some residents, but community participation remains low. In terms of integration, coordination among BPBD, PERKIM, the nagari government, and customary leaders has been carried out, yet policy communication and public understanding remain limited. In terms of adaptation, basic facilities and empowerment programs have been provided, but residents still face difficulties related to livelihoods, economic access, and socio-cultural attachment to their original settlement. Therefore, the effectiveness of this policy needs to be improved through stronger communication, community participation, economic recovery, and involvement of local customary leaders.